Dual-electrolyte aluminum/air microfluidic fuel cell with electrolyte-recirculation. (20th August 2021) - Wang, Lei; Cheng, Rui; Wang, Wentao; Yang, Guandong; Leung, Michael K.H.; Liu, Fude; Feng, Shien-Ping
Abstract: Aluminum/air microfluidic fuel cell (MFC) combines the advantages of co-laminar MFC and aluminum/air batteries with high energy density, low cost, membraneless and miniaturized design, which is a promising device to power the numerous nodes in the Internet of Things (IoT) ecosystems. Here, we propose a recirculating dual-electrolyte aluminum/air MFC with an alkaline anolyte and an acid catholyte. The cell exhibits an outstanding performance with an open-circuit voltage of 2.2 V and a short-current density of 1 A cm −2, benefiting from the dual-electrolyte design. In order to prevent the naturalization reaction between the electrolytes and improve the utilization rate, a regular hierarchical porous carbon paper is applied as the separator, which minimizes the mixing of electrolytes and facilitates the recirculation. This work provides an alternative route for cost-effective and high-performance aluminum/Air MFCs toward real applications.